A revised approach to productivity convergence in long-term scenarios - Guillemette, Yvan; Kopoin, Alexandre; Turner, David; De Mauro, Andrea (Paris, 2017)
"The paper describes revisions to the trend labour efficiency component of the production function underpinning long-term economic scenarios. The main goal of the revision is to add more policy and institutional determinants in the equation to enrich the scenarios that can be constructed. In the proposed equation, equilibrium trend labour efficiency depends on a broad measure of the quality of institutions and governance (the World’s Bank rule of law indicator), human capital (based on average years of schooling attainment), product market regulation (PMR), openness to trade adjusted for country size, the stability of the macroeconomic framework (based on inflation and its variance), income inequality (based on GINI coefficients) as well as domestic and global research and development (via accumulated stocks of R&D). Apart from the innovation effects, the sizes of the other effects are jointly estimated in a conditional convergence framework with a sample of about 120 countries, without the use of country fixed effects. Rule of law and openness are also estimated to influence the speed of convergence toward the long-term equilibrium."